2005
DOI: 10.1103/physreve.72.011601
|View full text |Cite
|
Sign up to set email alerts
|

Double dendrite growth in solidification

Abstract: We present experiments on the doublon growth morphology in directional solidification. Samples used are succinonitrile with small amounts of poly(ethylene oxide), acetone, or camphor as the solute. Doublons, or symmetry-broken dendrites, are generic diffusion-limited growth structures expected at large undercooling and low anisotropy. Low anisotropy growth is achieved by selecting a grain near the {111} plane leading to either seaweed (dense branching morphology) or doublon growth depending on experimental par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 31 publications
3
17
0
1
Order By: Relevance
“…The orientational dependence of the free energy of the solid-liquid interface has been established experimentally and theoretically as a primary parameter governing nonequilibrium crystal growth (Kurz and Fisher 1990;Glicksman and Marsh 1993;Billia and Trivedi 1993). For moderate undercooling, low g, and modest fluid viscosities, the tips of the crystal trunks tend to split regularly in the center, corresponding to the "doublonic" growth mode (Utter and Bodenschatz 2005). This leads to a somewhat disordered crystallization morphology that has some resemblance to naturally occurring seaweed.…”
Section: Ideal Dendritic Crystallization In Polymer Films: Mullins-sementioning
confidence: 97%
See 1 more Smart Citation
“…The orientational dependence of the free energy of the solid-liquid interface has been established experimentally and theoretically as a primary parameter governing nonequilibrium crystal growth (Kurz and Fisher 1990;Glicksman and Marsh 1993;Billia and Trivedi 1993). For moderate undercooling, low g, and modest fluid viscosities, the tips of the crystal trunks tend to split regularly in the center, corresponding to the "doublonic" growth mode (Utter and Bodenschatz 2005). This leads to a somewhat disordered crystallization morphology that has some resemblance to naturally occurring seaweed.…”
Section: Ideal Dendritic Crystallization In Polymer Films: Mullins-sementioning
confidence: 97%
“…The following image shows that polymer dendrites have long been observed on surfaces of polymer solutions. (d) Ni/Cu dendrite grown within the phase-field theory using a sixfold symmetry (k ¼ 6) of the interface free energy anisotropy Encyclopedia of Polymers and Composites DOI 10.1007/978-3-642-37179-0_30-1 # Springer-Verlag Berlin Heidelberg 2013 studied by Bodenschatz and coworkers (Utter and Bodenschatz 2005;Utter et al 2001). In the blends of mass ration 40/60-30/70, well-formed symmetric dendrites are observed, in which the fourfold symmetry of equilibrium PEO crystallization asserts itself at a macroscopic scale ( Fig.…”
Section: Ideal Dendritic Crystallization In Polymer Films: Mullins-sementioning
confidence: 98%
“…Accumulation of solute and heat at the interface sometimes produces super cooling, which introduces instability in the interface at all points, thus producing a tree‐like structure, called “ dendrite ,” in the resulting solid. It is now known that surface tension isotropy and anisotropy of the liquid melt, diffusion, super cooling, etc., play significant roles in deciding dense branching morphology or seaweed growth 27 . Super cooling can be constitutional super cooling or simple thermal super cooling 28 .…”
Section: Resultsmentioning
confidence: 99%
“…It is now known that surface tension isotropy and anisotropy of the liquid melt, diffusion, super cooling, etc., play significant roles in deciding dense branching morphology or seaweed growth. 27 Super cooling can be constitutional super cooling or simple thermal super cooling. 28 In the literature of carbothermic synthesis carried out in electric arc and thermal plasma, one finds that Si(l) participation in SiC growth has been highlighted by several workers.…”
Section: Resultsmentioning
confidence: 99%
“…The seaweed structure seems to grow with an angle of~40 deg to the trunk initially, but then bends to a larger angle (~60 deg). Prior studies have observed seaweed-like structures during solidification either at near-isothermal conditions [24][25][26][27] or in deeply undercooled metallic melts. [28][29][30] Textured seaweed structures were also observed by Rappaz et al [8][9][10]19] in aluminum alloys when zinc was added at compositions of 25 to 55 wt pct.…”
mentioning
confidence: 99%